Application of Lean Manufacturing Tools (5S, Andon and Standard Time) to Increase Productivity in the Production Area of a Metalworking Company - Bravo Fernandez, Jose Andres (2023)
This research focuses on the analysis of the causes of low productivity in the production area of a metalworking company. It also aims to implement Lean Manufacturing tools (5S, Andon and standard time) to increase the company’s productivity. The insertion of these tools begins with an initial diagnosis by means of a value stream map. It is followed by the identification of root causes, the implementation of the tools and the evaluation of results in a period from April to September 2022. The final results were an increase in average productivity, which went from 0.26 tn/soles to 0.33 tn/soles, that is to say, the increase in productivity was achieved in the company under study.